Analysis and design of the plug-in type repetitive control system based on steady-state residual convergence ratio. (10th June 2019) - Jiang, Xianliang; Hong, Huajie
In the feedback control robotic systems, the repetitive control method has a high control performance for the track or elimination of the periodic signals. The promotion of the plug-in type configuration of the controller broadens the application range and applicability of the control method. In this article, a novel design algorithm based on the steady-state residual convergence ratio of the repetitive control system is proposed to improve the performance of the stabilized platform to resist the periodic perturbation. The basic structure and stable condition of the plug-in type repetitive control method are first introduced by applying the small gain theorem and the stability theorem for time-lag systems. Then the analysis of the convergence rate is utilized in constructing the basic index of the design algorithm of a plug-in type repetitive control system based on a steady-state residual convergence ratio. The parameters of the designed controller are checked by the validity condition of the plug-in type repetitive control system, and a simulation example is given to verify the effectiveness of the design algorithm. The article provides basic design guidelines and schemes for the design of the periodic disturbance suppression performance of the feedback control system. In the final physical prototype experiment, the prospective steady-state residual convergence ratio is basically achieved within the allowable range of error.